Plan estratégico para la elaboración del presupuesto participativo del Gobierno Autónomo Descentralizado del cantón Mocache - Vivas Izurieta, Javier Alexander (2012)
The objective of this research is to create the strategic plan to develop the participatory budget of the Gobierno Autónomo Descentralizadodel Canton Mocache. The county has 38,392 inhabitants Mocache census INEC 2012 and with annual growth rate of 1.52% with a projected equation inhabitants in the year 2012 leaving 39,560 people, once we got the people proceeded to perform shows that gave us a total of 396 surveys, which do in Canton in both rural and urban, these surveys failed participatory budgeting data and citizen participation and commitments of its authorities, also conducted interviews with three officials and a representative town meeting, where we obtained data about strategic planning in the canton. For this we made a diagnosis of the current situation regarding Mocache City citizen participation and a strategic plan SWOT framed this standpoint dese and institutional citizen identified as key threats lack of planning as it is lived day and the lack of a culture of participation. Thus aspects have been identified that would govern the participatory budget of this county, in turn knowing local actors to which I would draw or change agents of democracy, with a great strength to this modern management system as there is a cantonal assembly and this will help a lot in the implementation of this Plan. In operational planning know the entire structure of this plan as its mission, vision and principles, and also the whole schedule of activities and each of its steps for implementation.